2012
DOI: 10.3109/08923973.2012.698622
|View full text |Cite
|
Sign up to set email alerts
|

Sargaquinoic acid isolated fromSargassum siliquastruminhibits lipopolysaccharide-induced nitric oxide production in macrophagesviamodulation of nuclear factor-κB and c-JunN-terminal kinase pathways

Abstract: Nitric oxide (NO) is a crucial molecule in inflammatory diseases and is synthesized from L-arginine by a specific enzyme, NO synthase (NOS). The expression of inducible NOS (iNOS) is activated in macrophages by various stimuli, such as lipopolysaccharide (LPS), a wall component of gram-negative bacteria. LPS binds to toll-like receptor 4 (TLR4) on the macrophage surface and activates several downstream signaling pathways, including mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB pathways. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…TLR4 triggers activation of MAPK/NF-kappa B signaling pathways to induce iNOS gene overexpression [ 29 ], and the TLR4-mediated signaling pathway also rapidly activates the PI3K/Akt signaling pathway to negatively regulate iNOS gene expression [ 23 , 30 ]. PNFS had an obvious suppressive effect on LPS-activated TLR4 mRNA overexpression, suggesting that PNFS could inhibit the overproduction of NO and the overexpression of iNOS by blocking the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 triggers activation of MAPK/NF-kappa B signaling pathways to induce iNOS gene overexpression [ 29 ], and the TLR4-mediated signaling pathway also rapidly activates the PI3K/Akt signaling pathway to negatively regulate iNOS gene expression [ 23 , 30 ]. PNFS had an obvious suppressive effect on LPS-activated TLR4 mRNA overexpression, suggesting that PNFS could inhibit the overproduction of NO and the overexpression of iNOS by blocking the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 activates signal transduction by the MyD88-dependent and MyD88-independent pathways, which in turn modulate inducible nitric oxygen synthase (iNOS) through tumor necrosis factor receptor-associated factor 6 (TRAF6), MAPK, NF-κB and other key genes. 43 Rahkola et al 44 found that patients with HR-HPV infection have higher nitric oxide (NO) in the cervical canal than do HPV-negative patients, indicating that the release of NO is closely related to HPV infection. The expression of iNOS in prostate cancer, head and neck squamous cell carcinoma, gynecological tumors, 45 breast cancer, and lung cancer tissues was different from that of normal tissue.…”
Section: Relationship Between Tlrs and Cervical Tumor Immunitymentioning
confidence: 99%
“…During our ongoing screening program designed to identify the anti-inflammatory potential of natural compounds, we isolated fucosterol, sargaquinoic acid, and sargachromenol from S. micracanthum by using activity-directed fractionation and characterized their structures using spectroscopy ( 1 H and 13 NMR, IR, and MS) as described previously [15]. However, the biological activities or modes of action of these compounds have not been reported previously, although another Korean group recently reported that sargaquinoic acid has anti-inflammatory activity [18]. Therefore, the present study investigated whether sargachromenol inhibited LPS-induced production of NO and PGE 2 , or the expression of iNOS and COX-2 proteins, through the inhibition of I κ B- α in macrophages.…”
Section: Introductionmentioning
confidence: 99%